2012
DOI: 10.1016/j.cirpj.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient process planning for CNC machining

Abstract: Machining is one of the major activities in manufacturing industries and is responsible for a significant portion of the total consumed energy in this sector. Performing machining processes with better energy efficiency will, therefore, significantly reduce the total industrial consumption of energy. In this paper, a framework is presented to validate the introduction of energy consumption in the objectives of process planning for CNC machining. The state of the art in process planning and energy consumption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(106 citation statements)
references
References 28 publications
0
92
0
2
Order By: Relevance
“…Currently, most of these types of material are machined by grinding or electro-discharge (EDM) processes [2]. These processes are time-consuming and expensive, and contemporary companies find savings at every stage of production [3]. For the manufacture of WC-Co parts (for example, punches and construction parts), which are characterized by a high degree of hardness, high resistance to wear, and low surface roughness [4][5][6][7], alternative methods of production can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most of these types of material are machined by grinding or electro-discharge (EDM) processes [2]. These processes are time-consuming and expensive, and contemporary companies find savings at every stage of production [3]. For the manufacture of WC-Co parts (for example, punches and construction parts), which are characterized by a high degree of hardness, high resistance to wear, and low surface roughness [4][5][6][7], alternative methods of production can be used.…”
Section: Introductionmentioning
confidence: 99%
“…In the first step we define and check an algorithm for feedrate correction for a plane surface for 5 tool trajectories type specific to plane machining [6].…”
Section: Resultsmentioning
confidence: 99%
“…The following cutter path will alter the geometry of this groove to leave a small cusp in the material. The size and shape of these cusps will categorize the roughness and appearance of the part [6]. The geometric properties of the surface will be dependent upon the cutter diameter, number of cutting flutes, the cutting speed, the step-over and the feedrate -factors that were studied widely in many researches.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics has shown that the greenhouse gas emitted from the usage of energy sources such as electricity, coal, oil and gas during manufacturing accounts for more than 37% even 50% of the world's total greenhouse gas emissions [38]. In order to balance the multi-faceted dimensions of economic growth and environmental protection, a series of regulations and guidelines, such as the European standard EN 16001:2010 [10], lifecycle carbon labeling outlined by the life-cycle assessment frameworks of the ISO 14040: 2006 and ISO 14044: 2006 [19,20], and the Publicly Available Specification 2050: 2008 (PAS 2050) [47], have been developing.…”
Section: Introductionmentioning
confidence: 99%